2021
DOI: 10.1021/acsanm.1c02582
|View full text |Cite
|
Sign up to set email alerts
|

Computationally Guided Design of Large-Diameter Carbon Nanotube Bundles for High-Strength Materials

Abstract: Large-diameter carbon nanotubes (CNTs) synthesized by floating-catalyst chemical vapor deposition (FC-CVD) assemble into bundles and subsequently into aerogel networks from which yarns and sheets are mechanically drawn. The CNT bundles exhibit unique microstructures with collapsed CNT packing, not found in other types of CNT yarns. At the same time, the bundle structure is not homogeneous and the wide variability of CNT cross-sectional shapes reflects the bundling process. Transmission electron microscopy (TEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Previous experimental and modelled studies have shown that flCNTs have distinctive flat regions and dumbbell-shaped end lobes. 3,28–31 In this study, only the flat region is modelled, similar to Patil et al , 18 Pisani et al , 19 Deshpande et al , 20 and Gaikwad et al 21 The dumbbell-shaped end lobes are excluded for computational efficiency, while the interaction of these dumbbell shaped end lobes can be accurately captured with mesoscale modeling. 32–34 In this study, each flCNT is modelled as two sets of graphene sheets representing the flat region of flCNTs.…”
Section: Molecular Modelingmentioning
confidence: 89%
“…Previous experimental and modelled studies have shown that flCNTs have distinctive flat regions and dumbbell-shaped end lobes. 3,28–31 In this study, only the flat region is modelled, similar to Patil et al , 18 Pisani et al , 19 Deshpande et al , 20 and Gaikwad et al 21 The dumbbell-shaped end lobes are excluded for computational efficiency, while the interaction of these dumbbell shaped end lobes can be accurately captured with mesoscale modeling. 32–34 In this study, each flCNT is modelled as two sets of graphene sheets representing the flat region of flCNTs.…”
Section: Molecular Modelingmentioning
confidence: 89%
“…Several experimental and modeling studies have shown that these flCNT sheets form dumbbell-shaped end lobes 8 , 13 16 and assume a conformation similar to that of bi-layer graphene (BLG) with connected edges. 14 , 17 , 18 A density functional theory (DFT) study by Hu et al 19 showed that end lobes exhibit reactivity and flexoelectricity.…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental and modeling studies have shown that these flCNT sheets form dumbbell-shaped end lobes , and assume a conformation similar to that of bi-layer graphene (BLG) with connected edges. ,, A density functional theory (DFT) study by Hu et al showed that end lobes exhibit reactivity and flexoelectricity. In this study, the end lobes are excluded as these features can be better captured with larger length scale models, and just the BLG portion of the flCNTs is directly modeled.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanotube (CNT) sheet and yarn reinforced bismaleimide (BMI) resin composites are being studied for use in extreme environments. , Improving their already strong mechanical properties could have a significant impact on the development of lightweight aerospace structures suitable for the harsh conditions encountered in space exploration, surpassing the performance of current carbon-fiber-reinforced composites. Well-aligned CNT bundle microstructures are crucial for the mechanical performance, but their dense packing , limits the ability of chemical treatments to improve the interfacial bonding properties between collapsed CNTs and between CNTs and the resin material. Figure S1a provides an example of a collapsed CNT, while Figure S1b shows graphitic-like dense packing of aligned collapsed CNTs, such as those identified in commercially available MIRALON manufactured by Nanocomp Technologies, Inc. and for which bilayer graphene serves as a representative basic structure.…”
mentioning
confidence: 99%
“…Well-aligned CNT bundle microstructures are crucial for the mechanical performance, but their dense packing , limits the ability of chemical treatments to improve the interfacial bonding properties between collapsed CNTs and between CNTs and the resin material. Figure S1a provides an example of a collapsed CNT, while Figure S1b shows graphitic-like dense packing of aligned collapsed CNTs, such as those identified in commercially available MIRALON manufactured by Nanocomp Technologies, Inc. and for which bilayer graphene serves as a representative basic structure.…”
mentioning
confidence: 99%